Poly(arylene ether ketone) with pendant pyridinium groups for alkaline fuel cell membranes. (27th April 2017) - Kim, Suji; Yang, Sungwoo; Kim, Dukjoon
Abstract: Using the step-growth polycondensation reaction, poly(arylene ether ketone) (PAEK) and activated poly(arylene ether ketone)-NHS intermediates (PAEK-N) were synthesized. PAEK-NHS intermediates with pyridinium groups (PAEK-PYR) were obtained by adding different amounts of PYR groups. The successful syntheses of PAEK, PAEK-N, and PAEK-PYR were confirmed by nuclear magnetic resonance spectroscopy and Fourier transform infrared spectroscopy. Several important membrane properties (e.g., ionic exchange capacity (IEC), water uptake, anion conductivity, and thermal and mechanical stability) were investigated for their applications in alkaline fuel cells. Water uptake, swelling ratio, anion conductivity, and IEC increased with increasing PYR contents, while the mechanical properties decreased. Among a series of prepared membranes, the PAEK-PYR100 and PAEK-PYR125 membranes showed IEC and anion conductivity values that were higher than those of a commercial AHA membrane. Also, all of the prepared membranes were thermally stable up to 255 °C and show excellent chemical stability in alkaline conditions. Highlights: PAEK-PYR anion exchange membrane was synthesized via polycondensation reaction. PAEK-PYR100 and PAEK-PYR125 showed higher conductivity than commercial AHA membrane. PAEK showed even superior chemical stability than AHA membrane in alkaline condition. Peak power density of cell prepared from PAEK was higher than that from AHA membrane.